Mennonites in the global village - Driedger, Leo, 1928- (Book collections on Project MUSE., 2000)
"Leo Driedger explores the impact of professionalism and individualism on Mennonite communities, cultures, families, and religion, particularly in light of the scholarly work of futurists Alvin and Heidi Tofler, which has described the shift from a homogeneous industrial society to a diversified electronic society. Driedger contends that Mennonites are in a unique position in meeting the electronic challenge, having entered modern society relatively recently. He traces trends in Mennonite life by reviewing such issues as the shift from farming to professionalism, the role of mass media, and increased social interaction. Mennonites face many of the challenges that other religious minorities in North America encounter in the move to modernity, and this study provides in-depth insights into this transition."--Jacket